«Ժողովրդավարական համախմբում» հասկացության քաղաքագիտական մեկնաբանության շուրջ - Սարգսյան, Առնակ (YSU Journal of International Affairs, 2018)
The article examines the concept of democracy as a form of government when the government is responsible for the actions of its citizens, and citizens carry out their interests through the representatives elected by them, in the conditions of their competition and cooperation. Democracy cannot be consolidated if the democratic transition is not over. It is considered to be completed when all the branches of government – legislative, executive, and judicial, are largely independent of the military, religious and other authoritarian institutions.
Keywords: waves of democratization, transformation, democratic consolidation, “hybrid” regime, competition, development, legitimacy